Restructuring Nepal as A New Nation: An Administrative Geographic Prospective for Devolution of Power and Evolution of Socio-Cultural Transformation - Panday, Ram Kumar (Socio-Economic Development Panorama, 2009)
Spatial regionalization is one of the challenging tasks for implementation of overall development strategy in a country like Nepal. Although administrative units have been divided in different political periods, still there is enough room to plan for effective mobilization of resources and through efficient participation of the people. It requires fulfillment of sustainable self reliance modulation of a geographic area ruling a nation of diversities and disparities. Nepal still lacks academic works on administrative geography. To fulfill the stipulated objectives, secondary data and empirical methodology have been used for the interpretation and analysis of facts and figures. Different approaches have been discovered to facilitate to study administrative geographic problems. The findings of the study suggest that development can be accelerated following proper devolution, inclusion, decentralization and resource mobilization. Self-reliance and sustainability can be achieved through scientific geographic planning of administrative units. To achieve automation of development acceleration, different modules of restructuring the nation have been recommended. Incorporating self-sustained development strategy requires giving space to geographic approach in using land as well as regionalization of the distinct geographic sub-regions that covers cultural character. This recommendation helps to harness full potentialities of Nepali native nature. Administrative geography can be a way out to find a solution in the governance, and achieve high development performances at an accelerated pace. Key words: Administrative geography; village municipality; bulb change model; altitude geography; conflict management; multi-culture; decentralization; devolution; inclusion; local self government; administrative divisions; regionalism; spatial structure; regional Socio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June